Kepemimpinan Kepala Sekolah dan Iklim Sekolah Terhadap Kinerja Guru SMP Negeri Kota Jambi - Mulyadi; Mohamad Muspawi; Dini Apriliani (STAI Terpadu Yogyakarta, 2023)
This study aims to reveal the relationship between the principal's leadership and school climate on the performance of teachers of SMP Negeri Kota Jambi. The research method used was a Korean study with a sample of 220 people using theecnik cluster random Simpling. The research instruments used are rating scales and Likert Scale model questionnaires that have been tested for validity and reliability. The research data were analyzed using pearsoncorrelation and regression techniques. The results of the data analysis showed that: (1) the principal's leadership contributed significantly to teacher performance by 24.4%. The results of the principal's leadership achievement level are in the good category, so that the increase in the principal's leadership is directly proportional to the increase in teacher performance; (2) School climate contributes significantly to teacher performance 36.9%. Furthermore, the results of the analysis of the description of climate variable data of Jambi City State Junior High School are generally known to be still in the conducive category with a score of 86.83%, so that it can be seen that the built school climate is able to provide comfort for teachers in doing their work; (3) The principal's leadership and the school climate together contribute to teacher performance by 51.6%. The better the leadership exercised by the principal, the more conducive the school climate is, and the better the teacher performance, data analysis shows that teacher performance is significantly influenced by the principal's leadership and school climate, both individually and collectively.